Relationship between speech perception and production skills and morphosyntactic development in Spanish-speaking children with Speech Sound Disorders - Zarzo Benlloch, Miriam; Ygual Fernández, Amparo; Cervera Mérida, José Francisco (Revista de Investigación en Logopedia, 2021)
Research into grammatical development and its possible relationship with speech processing deficits in children with a speech sound disorder (SSD) is scarce, especially for the Spanish language. The purpose of this work was to analyse the influence of speech perception and production skills on the morphosyntactic development of preschool-age children with SSD. A sample of 52 Spanish-speaking children aged 4 to 6 years was studied: 26 had SSD and 26 had typical development (TD); they were matched by their chronological age, nonverbal intelligence quotient, and receptive vocabulary level. Morphosyntactic development was evaluated with three CELF-Preschool-2-Spanish language subtests: Word structure, Recalling sentences, and Sentence structure. Speech perception was assessed with phonological discrimination and recognition tasks with minimal pairs, and speech production was checked with an image-naming task. Children with SSD had significantly poorer scores than those with TD in measurements related to morphosyntactic development, perception, and speech production. Mediation analysis showed that there was a positive effect between the mediation of speech production and both speech perception and grammatical development. Children with SSD and without LD, presented worse morphosyntactic development than those with TD, even in cases of mild—moderate speech disorder. These children appear to learn language differently because they ineffectively extract, manipulate, and produce speech characteristics. Grammatical development does not appear to be independent of speech processing skills and, furthermore, it also seems to depend on several factors including speech perception and production, and the synergistic effect these two processes have on each other.